Pengaruh Kompres Hangat Terhadap Intensitas Nyeri Pada Pasien Dyspepsia di IGD Rumah Sakit Tingkat II. Robet Wolter Mongisidi Manado - Vanessa Datunsolang; Silvia Dewi Mayasari Riu; Faradilla Miftah Suranata (STIKES Columbia Asia Medan, 2023)
Dyspepsia is a medical condition characterized by pain or discomfort in the upper abdomen or solar plexus. Heartburn in dyspepsia sufferers occurs because the sphincter muscles in the esophagus and stomach do not close completely, resulting in a back-flow of stomach acid into the esophagus. A behavior to reduce pain in dyspepsia patients is a warm compress. The aim of this study was to determine the effectiveness of warm compresses on pain intensity of dyspepsia pain patients on Emergency Room of at Robert Wolter Mongisidi Hospital Manado. The method in this research is a quasi experiment with one group pre-post test. With 10 peoples of samples taken by using accidental sampling. Data collection uses SOPs and observation sheets. Next, the collected was processed using the Mc-Nemar test.The results of this study showed the majority of subjekts experienced changes after applying a warm compress (90%). The results of data analysis tested using Mc-Nemar obtained a value of p=0.031 (a<0.05), meaning there was an effect of warm compresses on pain intensity in dyspepsia patients in emergency room at Robert Wolter Mongisidi Hospital Manado.The conclusion, the compresses on the intensity of pain in dyspepsia patients in the Emergency Room at Robert Wolter Mongisidi Hospital Manado. It is recommended for the hospitals staff and dyspepsia sufferers to apply warm compresses to help reduce pain.